Thermo-sensitive Hydrogel Incorporating Maleic Anhydride Modified Microcrystalline Cellulose. Issue 2 (February 2020) - Zhang, Ting; Zheng, Nan; Luo, Jianfang; Cai, Huiling; Li, Yanghao; Zhai, Jia; Peng, Xinyi
Abstract: The thermo-sensitive hydrogel incorporating maleic anhydride modified mcirocrystalline cellulose was prepared by two steps. At first, the mixture of maleated and fumarated celluloses were produced by a solvent-free procedure, in which the biopolymer was added to molten maleic anhydride. Secondly, the photo-polymerization of n-isopropyl acrylamide (NIPAM) with the modified biopolymer was carried out in water/NaOH/urea/thiourea solution by using 1173 as the photo-initiator. The derivatives were characterized by FTIR and SEM. It was a clear temperature dependence on the volume of the grafted hydrogel in deionized water that generated by the coil-to-globule transition of poly (NIPAM) in aqueous media from the lower critical solution temperature (LCST) of PNIPAM to the upper critical solution temperature (UCST). From the absorbance of the gel to methylene blue, it was shown that the quasi-second-order kinetics could fit the experimental data well.